J. Nelson Wisner, Ordinances and By-Laws of the Corporation of Martinsburg: Berkeley Co., West Virginia, Including the Act of Incorporation and All Other Acts of a Special or General Nature, at 25, An Ordinance to Prevent Certain Improper Practices Therein Specified, § 3 (1875) - (:unkn) unknown (General Publisher, 1875)
If any person shall fire or discharge within such parts of the town which are or shall be laid out into lots, or within two hundred yards of said limits, any cannon, gun, pistol or fire-arms, or any cracker, squib, rocket or fire-works, except it be in case of necessity, or in the discharge of some public duty, or at a military parade by order of the officer in command, or with the permission of the Mayor or Council of the town, such person for every such offence shall forfeit any pay to the town not less than one nor more than five dollars.
--
Keywords: DISCHARGE